2008
DOI: 10.21608/mjae.2008.190137
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Potato Water Content Using Nir Diffuse Reflection Method

Abstract: Spectroscopic techniques with near infrared (NIR) method has been used for the compositional, functional and sensory analysis of food ingredients, process intermediates, and final products all over the world. This study demonstrated a potential way to predict water content in potatoes (Diamant variety) using electric heater, spectroscopy within visible (VIS) and near infrared (NIR) spectral data.The data was selected to establish a prediction models to estimate potato water content (with or without skin). Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
0
1
Order By: Relevance
“…The Royal variety had the highest moisture content (77.08%), while Shangi had 76.56% and Dutch Robjin had the least with 76.42%. These findings are lower than those reported by other researchers (Elbatawi et al, 2008;Zhang et al, 2018). However, these values are in agreement with other studies where similar findings have been reported (Hafezi et al, 2015;Sablani & Mujumdar, 2006;Xiao et al, 2011).…”
Section: Moisture Content Of Potato Varietiescontrasting
confidence: 67%
“…The Royal variety had the highest moisture content (77.08%), while Shangi had 76.56% and Dutch Robjin had the least with 76.42%. These findings are lower than those reported by other researchers (Elbatawi et al, 2008;Zhang et al, 2018). However, these values are in agreement with other studies where similar findings have been reported (Hafezi et al, 2015;Sablani & Mujumdar, 2006;Xiao et al, 2011).…”
Section: Moisture Content Of Potato Varietiescontrasting
confidence: 67%